TEKS TUTUR CANDRABHERAWA: ANALISIS STRUKTUR DAN FUNGSI - Ayu Puspita Dewi, Ni Nyoman; Suteja, I Wayan; Darsana, I Nyoman (Humanis; Volume 16. No. 2. Agustus 2016, 2016)
The study about Tutur Candrabherawa is aimed at analyzing the structure and the function. The theory used in this study was structural and function theory by Teew, Damono, and Ratna. The methods used were reading, noting technique with translating technique, qualitative method descriptive analytic technique, and informal method, educative inductive technique. The results of this study showed the structure and function found in the text. Forma structure included figurative language. meanwhile narative structure included incident, plot, characters and characterization, setting, theme, and moral values. the functions contained in the text were tattwa function(philosophy), kewiraan/ksatria function, and kawisean (magic) function from the characters Yudisthira and Candrabherawa.